Value Vectors of the World Local Orthodox Churches Position Regarding Russia's War Against Ukraine - Бродецький, Олександр; Горохолінська, Ірина; Лагодич, Микола (My University, 2022)
The article deals with the religious contexts of the modern civilizational crisis caused by Russia’s war of aggression against Ukraine. Among the multitude of thematic lines of this set of problems, the article’s authors focus their attention precisely on the position of the world Orthodox Churches regarding this war. The concentration of such attention is objectively determined by the fact that the majority of Ukrainian citizens position themselves as Orthodox by faith, and therefore, are particularly sensitive to the opinion of the leaders of the Orthodox Churches of the world. The article examines the value aspects of the problem of a just peace and considers alternative moral positions about this. Further, with reference to published documents and sources, the article classified the position of the governing structures of the world Orthodox Churchesregarding the current war in Ukraine. The positions of autocephalous Churches are considered, and also some of the Churches jurisdictionally subordinate to autocephalous ones. The research is interdisciplinary including religious studies, ethics, social philosophy, and political science. The data of the latest sociological studies in Ukraine are considered.
Keywords: peace; war; government; the Orthodox; Ukraine; the World Orthodox Churches; state-aggressor; value positions; religious leadership